Drying and roasting of cocoa and coffee / Ching Lik Hii; Flávio Meira Borém - Borém, Flávio Meiraedited by
"The drying and roasting of cocoa and coffee beans play critical roles in governing the formation of flavor precursors in the early stage and also development of flavor and aroma in the later stage during processing. Hence, qualities of the finished chocolates and coffee powder products are affected greatly by the dried and roasted beans produced. This book discusses the principles and practices of drying and roasting of cocoa and coffee beans, processing equipment, flavor chemistry, and safety and quality. The book will also include recent scientific studies and developments and also from the authors whom are leading experts in the drying and roasting aspects of cocoa and coffee processing."-